Towards causal mechanisms of consciousness through focused transcranial brain stimulation - Havlík, Marek; Hlinka, Jaroslav; Klírová, Monika; Adámek, Petr; Horáček, Jiří (Neuroscience of consciousness, 2023)
Conscious experience represents one of the most elusive problems of empirical science, namely neuroscience. The main objective of empirical studies of consciousness has been to describe the minimal sets of neural events necessary for a specific neuronal state to become consciously experienced. The current state of the art still does not meet this objective but rather consists of highly speculative theories based on correlates of consciousness and an ever-growing list of knowledge gaps. The current state of the art is defined by the limitations of past stimulation techniques and the emphasis on the observational approach. However, looking at the current stimulation technologies that are becoming more accurate, it is time to consider an alternative approach to studying consciousness, which builds on the methodology of causal explanations via causal alterations. The aim of this methodology is to move beyond the correlates of consciousness and focus directly on the mechanisms of consciousness with the help of the currently focused brain stimulation techniques, such as geodesic transcranial electric neuromodulation. This approach not only overcomes the limitations of the correlational methodology but will also become another firm step in the following science of consciousness.
Keywords: inhibition; mechanisms of consciousness; causal explanation; transcranial electric stimulation; excitation; neural correlates of consciousness; consciousness; brain stimulation; geodesic transcranial electric neuromodulation